Value of chlortetracycline-sulfamethazine supplementation for beef calves after being weaned and shipped - Drake, C.L.; Smith, E.F.; Perry, H.B.; Good, D.L.; Richardson, D. (Kansas Agricultural Experiment Station, 2011)
The number of cattle concentrated in small areas is increasing in Kansas. Conditioning new cattle is a major problem in some operations. This experiment studied effects of adding a combination of chlortetracycline-sulfamethazine on weight gain, feed efficiency and general health when fed to beef calves after they were weaned and shipped.
Keywords: Beef; Gain; Chlortetracycline-sulfamethazine; Feed efficiency; Health